PENGAMANAN PESAN TEKS E-MAIL MENGGUNAKAN METODE ALGORITMA BIFID DAN FEEDBACK CIPHER - Wulandari, Siska (JURIKOM (Jurnal Riset Komputer), 2019)
One of the most widely used internet applications is electronic message sending, called e-mail. As time goes by, sending messages via e-mail becomes one of the important things. But there are some threats that do not know when using e-mails such as eavesdropping on e-mail contents, changing e-mail contents by unauthorized people and making e-mails no longer authentic. The technique of securing text messages or data is known as cryptography. In cryptography there are several methods that are quite important in securing data, to maintain data confidentiality one of which is encryption (coding). Decryption (original text) of one of the cryptographic algorithms, namely bifid cipher and feedbak cipher. Bifid cipher was first discovered by Felix Delastelle in 1901. Bifid cioher encrypts by randomizing the position of the row and column of letters in the message that corresponds to the 5X5 square key board while the Cipher Feedback Method uses the Shift Register system, which is processed first is the Initialization Vector in the Encryption with Key algorithm. After processing, the resulting bits will go through a bit selection process, usually the leftmost bits, then encrypted with Plaintext to produce the Ciphertext. By applying a combination of the two algorithms, the bifid cipher algorithm and the feedback cipher, it is expected that the message sent in the e-mail will be coded so that unauthorized parties do not know the meaning of the message being sent. And can maintain the authenticity of the messages sent